Formulation of Empowering Poor Women with Pro-Poor Capacity Improvement Model - Esy Nur Aisyah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
There are several reasons that lead to the importance of implementing a gender-oriented poverty alleviation program, one of which is that it can stimulate the emergence of empowerment. So the purpose of this research is to formulate the empowerment of poor women with the Pro-poor Capacity Improvement model in an effort to alleviate poverty in rural areas. The formulation of the model is based on the analysis of potentials, barriers, opportunities, threats, and policies in empowering poor women. Research in Gadingkulon Village, Dau District, Malang Regency was carried out through questionnaires, in-depth interviews, observations, Focus Group Discussions (FGD), and literature studies. The first stage uses quantitative analysis to present the frequency table, and the second stage uses qualitative analysis in gender analysis by Sara Longwee. This research resulted in a model for empowering poor women, which was designed in the Pro-poor Capacity Improvement ((PCIM) model which consisted of several components in the model in order to improve family welfare. These components consisted of the results of an analysis of potential, opportunities, obstacles, intervention in entrepreneurship, and welfare.The formulation of empowerment of poor women in Gadingkulon Village can be implemented in poverty alleviation efforts.